Teaching and learning spoken French at elementary level. French teaching as seen from the perspective of the observers and the learners - Imgrund, Bettina (Swiss Journal of Educational Research, 2018)
Learners’ acceptance of French as a school subject is largely dependent on lesson structure and learning success in oral competence. The project FRANZEL- Good French Teaching at Elementary Level explores the connection between the quality of foreign language teaching methodology and competence gain. This article presents the first answers to the central question which features of the teaching and learning process support the acquisition of oral competence for learners of French in 6th grade primary. Towards this focus, the following topics will be discussed: What constitutes good French teaching? How can it be researched? What empirical evidence can be provided?